(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
Pedagogical conditions are conditions that ensure the effectiveness of the pedagogical system and the success of the pedagogical process. Pedagogical conditions mean a set of possibilities, methods, organizational forms and material possibilities of its implementation.